2013
DOI: 10.1097/pec.0b013e3182a219d0
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Inhaled Steroid Treatment for Children With Asthma in the Emergency Room

Abstract: Emergency department physicians report low rates of ICS prescribing. Commonly cited barriers include unclear guidelines, believing that long-term medication prescribing is not within their role, and inability to see patients in follow-up. Addressing guideline discrepancies may improve preventive care delivery in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Ensuring the proper medications and devices are prescribed, picked up from the pharmacy, and are available for use is crucial for proper asthma care. Many roadblocks interfere with this process, including parent-child relationships, 54 disjointed care, providers not prescribing necessary medications, 5556 familial beliefs, understanding or attitudes regarding the prescribed medications themselves or their necessity, 5758 caregiver stress and depression, language barriers, and cost of medications. Leading open discussions to patient specific barriers to medications, encouraging medications to be brought with on every visit and addressing the medication reconciliation in a deliberate way may address some of these concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring the proper medications and devices are prescribed, picked up from the pharmacy, and are available for use is crucial for proper asthma care. Many roadblocks interfere with this process, including parent-child relationships, 54 disjointed care, providers not prescribing necessary medications, 5556 familial beliefs, understanding or attitudes regarding the prescribed medications themselves or their necessity, 5758 caregiver stress and depression, language barriers, and cost of medications. Leading open discussions to patient specific barriers to medications, encouraging medications to be brought with on every visit and addressing the medication reconciliation in a deliberate way may address some of these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…spacer) and new devices with different techniques continue to be released. 55 Lack of standardization of correct inhaler technique steps is an additional problem. National guidelines for technique and systematically measuring inhaler technique in the office are necessary to improve medication delivery in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of this project overcoming cultural barriers to providing preventive care delivery in the PED was critical. As our survey noted, many ED physicians reported that prescribing long-term medications is outside their role [9]. This belief likely contributed to delays in the success of our interventions.…”
Section: Discussionmentioning
confidence: 75%
“…In addition to being more clinically effective, we determined that prescribing or dispensing ICS at the time of ED discharge would also generate cost-savings. We then developed a survey to assess the current rates of ICS prescribing among members of the American Academy of Pediatrics Section on Emergency Medicine [9]. The majority of respondents reported prescribing ICS 25% of the time or less and cited unclear guidelines, a belief that long-term medication prescribing is not within their role, and an inability to see patients in follow-up as important barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The strong endorsement of specific training sessions, decision-support tools, reminders, and pharmacy reports of drug claims to support the general management approach is aligned with prior studies [ 32 ]. In these studies, physicians voiced, as barriers to optimal asthma management, their confidence about capabilities in prescribing, and beliefs about consequences of, long-term ICS, as well as their worry about patients' noncompliance and the absence of patient follow-up [ 10 , 33 , 34 ]. In addition, key resources that increase physician's reported comfort in prescribing long-term ICS and perceived patient adherence were endorsed for patient-specific management, presumably because of more certainty in the management decision (i.e., lung function testing, specialist's opinion, and access to an asthma clinic), greater degree of collaborative care and patient follow-up (i.e., patient guidance and education provided by a paramedical healthcare professional) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%